The efficiency of the principle of celerity in maintenance disputes, a guarantee of protection of the best interests of the child - Anrango Serrano , Isabel Cristina (2025)
This study examines the application of the principle of procedural speed in child support cases in Ecuador and its relationship to ensuring the best interests of the child. The objective was to analyze the extent to which the lack of effectiveness of this principle limits the timely protection of child support rights. The research used a mixed approach: document review and theoretical analysis, supplemented by surveys of 139 justice operators in the city of Ibarra. The results show that, although 78.4% recognize the importance of speed, more than 61% perceive deficiencies in its application due to judicial overload, bureaucracy, and lack of resources. Likewise, 81.9% consider it necessary to reform regulations to establish strict deadlines, simplify procedures, and strengthen specialized training. The proposal includes prior mediation, the exclusive use of SUPA, and inter-institutional interoperability. It concludes that the lack of procedural speed violates the rights of children and adolescents, and that the adoption of reforms is an essential way to ensure more agile and effective access to justice.